THE ARMORICA 'MICROPLATE': FACT OR FICTION? CRITICAL REVIEW OF THE CONCEPT AND CONTRADICTORY PALAEOBIOGEOGRAPHICAL DATA - Robardet M. (My University, 2003)
The problem of an 'Armorica microplate', detached from Gondwana and having had during part of the Palaeozoic an independent latitudinal evolution, is reconsidered in terms of a critical review of the palaeomagnetic data that were the very roots of this concept and through an alternative approach based on palaeoclimatic and palaeobiogeographical data. Palaeomagnetic data for the Silurian and the Devonian of the south European regions supposedly constituting the Armorica microplate remain rare and ambiguous. Those from Gondwana are more numerous but contradictory enough to give rise to diverging models regarding the latitudinal evolution of this continent. Consequently, the reality of an Armorica microplate cannot be considered as established. On the contrary, lithological indicators of palaeoclimate and palaeobiogeographical data are in total harmony and indicate that, in actual fact, the southern European regions remained permanently closely connected with Gondwana, of which they composed the northern margin. Although repeatedly maintained for more than 20 years, the concept of an Armorica microplate can thus be considered a fiction. This conclusion should lead to the dismissal of geodynamical models proposed for the Variscan Belt to which this concept was integrated and are contradicted by inescapable palaeobiogeographical constraints.
Keywords: PALAEOZOIC; PALAEOGEOGRAPHY; ARMORICA MICROPLATE; PALAEOMAGNETISM; PALAEOBIOGEOGRAPHY; VARISCAN BELT; Devonian; Silurian; Paleozoic::Devonian; Paleozoic::Silurian; Палеозой::Девонская; Палеозой::Силурийская